Teachers' Perspectives on AI Integration in EFL Teaching: Perceived Benefits and Challenges - Syafrayani, Putri Rizki; Ayunda, Riska; Molina, Merry Luz; Hutasuhut , Mahmud Layan; Siregar, Masitowarni (Universitas Negeri Medan, 2024)
This study investigates English course teachers' perspectives on the integration of artificial intelligence (AI) tools, specifically ChatGPT, in English Language Teaching (ELT) within the informal education sector in Medan, Indonesia. Employing a qualitative approach, data were collected from 17 teachers through questionnaires to explore their experiences, perceived benefits, and challenges associated with AI integration. The findings reveal that 64.29% of teachers recognized AI's potential to streamline lesson planning and generate ideas, while 42.86% appreciated its ability to personalize instruction. Additionally, 14.29% highlighted its role in enhancing language skill practice. However, significant concerns emerged, with 50% of teachers fearing reduced teacher-student interaction and 42.86% worrying about AI undermining traditional teaching values. Ethical issues, including potential bias (14.29%) and misinformation (7.14%), were also noted. The study concludes that while AI offers transformative opportunities in ELT, its integration must be supported by teacher training, resource allocation, and a balanced approach to preserve human-centered teaching principles. These findings provide valuable insights for educators, policymakers, and researchers aiming to harness the potential of AI in language education.